Factors Associated with Recent HIV Testing among Heterosexuals at High Risk for HIV Infection in New York City - Gwadz, Marya; Cleland, Charles M.; Kutnick, Alexandra; Leonard, Noelle R.; Ritchie, Amanda S.; Lynch, Laura; Banfield, Angela; McCright-Gill, Talaya; del Olmo, Montserrat; Martinez, Belkis (Frontiers in Public Health, 2016)
Background. The CDC recommends persons at high-risk for HIV infection in the United States receive annual HIV testing to foster early HIV diagnosis and timely linkage to health care. Heterosexuals make up a significant proportion of incident HIV infections (>25%), but test for HIV less frequently than those in other risk categories. Yet factors that promote or impede annual HIV testing among heterosexuals are poorly understood. The present study examines individual/attitudinal-, social-, and structural-level factors associated with past-year HIV testing among heterosexuals at high-risk for HIV. Methods. Participants were African American/Black and Hispanic heterosexual adults (N=2307) residing in an urban area with both high poverty and HIV prevalence rates. Participants were recruited by respondent-driven sampling (RDS) in 2012-2015 and completed a computerized structured assessment battery covering background factors, multi-level putative facilitators of HIV testing, and HIV testing history. Separate logistic regression analysis for males and females identified factors associated with past-year HIV testing. Results. Participants were mostly male (58%), African American/Black (75%), and 39 years old on average (SD = 12.06 years). Lifetime homelessness (54%) and incarceration (62%) were common. Half reported past-year HIV testing (50%) and 37% engaged in regular, annual HIV testing. Facilitators of HIV testing common to both genders included sexually transmitted infection (STI) testing or STI diagnosis, peer norms supporting HIV testing, and HIV testing access. Among women, access to general medical care and extreme poverty further predicted HIV testing, while recent drug use reduced the odds of past-year HIV testing. Among men, past-year HIV testing was also associated with lifetime incarceration and substance use treatment. Conclusions. The present study identified gaps in rates of HIV testing among heterosexuals at high-risk for HIV, and both common and gender-specific facilitators of HIV testing. Findings suggest a number of avenues for increasing HIV testing rates including increasing the number and types of settings offering high-quality HIV testing; promoting STI as well as HIV testing; better integrating STI and HIV testing systems; implementing peer-driven social/behavioral intervention approaches to harness the positive influence of social networks and reduce unfavorable shared peer norms; and specialized approaches for women who use drugs.